The thermal evaluation of snow line and identification of potential areas of snow falling in the Alborz Mountains with NOAA-AVHRR images - Dariush Yarahmadi; Amanolah fathnia; Mehdi Sherafat (تحقیقات کاربردی علوم جغرافیایی)
Abstract The extention of Snow cover and its spatial and temporal changes considered as a basic parameter in climatic and hydrologic studies. Data from satellite images due to the low cost and the large extention of cover are, effectively help the identifying of the snowy basins. Since the satellites are able to imaging a surface at different times, this will allow snow survey studies to investigate the spatial and temporal distribution of snow. In this research, Snow line changes and the surface temperature line in Alborz Mountains using NOAA-AVHRR satellite images since 2006 from 2015 was studied. The results showed that at the study period, maximum area of snow have been observed in April 2015, with the amount of 12051 square kilometers and the minimum area snow have been observed in June 2008, with the amount of 33 square kilometers. The average of the lowest elevation of snow covered areas, have been observed in April 2007, with the amount of 2662 meters and its highest value have been observed in June 2008 with the amount of 3820 meters. Also the most of the snow line change occurred between the years 2007 to 2008. Moreover, in almost of 15 years, the isoterm of zero degrees Celsius, matches with the snow line and its elevation has changed as the snow area is changed.